SOUND PRODUCTION METHODS FOR CLASSICAL PERCUSSION INSTRUMENTS - Yannavut, Wannapha; Siripanichwattana, Tanasit (Mahidol Music Journal, 2024)
This research focuses on the significance of sound production on classical percussion instruments, emphasizing the study, data collection, and analysis required to develop practical exercises. A musical composition for tom-tom was provided to a group of nine students, who engaged in performance and practice after receiving notations for a full day. Sound recordings were made before and after practical training, during which students underwent hands-on training to understand the workings of different muscle groups, including fingers, wrists, arms, and shoulders. This training aimed to enable students to produce sounds with varying qualities such as loudness, softness, clarity, sharpness, shortness, length, depth, etc., corresponding to different symbols and notations. Subsequently, sound recordings from both sessions were processed using computer software, revealing a clearer understanding of sound production following targeted muscle training. This research contributes valuable insights into the ability to produce and manipulate sound according to specific requirements, symbols, and various notations, including the distinct representation of different parameters outlined in the composition.